Paleoarchean metamorphism in the Acasta Gneiss Complex: Constraints from phase equilibrium modelling and in situ garnet Lu–Hf geochronology - Kaempf, Jonas; Johnson, Tim; Clark, Chris; Alfing, Julian; Brown, M.; Lanari, P.; Rankenburg, Kai (2024)
The oldest known evolved (felsic) rocks on Earth (c. 4.03 Ga) are found in the Acasta Gneiss Complex (AGC) in north-western Canada and represent a fundamental keystone in unravelling the geological processes governing crustal growth and differentiation during the Hadean and early Archean. Although the timing of multiple episodes of magmatism, metamorphism and deformation in these tonalitic gneisses has been investigated extensively, the metamorphic pressure–temperature (P–T) conditions recorded by the rocks are poorly constrained. Here, we use phase equilibrium modelling coupled with in situ garnet Lu–Hf geochronology and trace element analysis for two garnet-bearing tonalitic gneisses to decipher the metamorphic history of the AGC. The observed mineral assemblages are consistent with peak metamorphic conditions of T = 725–780°C and P = 4.5–6.2 kbar and the generation of a small amount of melt (<7 vol.%). Garnet geochronology constrains the age of metamorphism to 3.3–3.2 Ga, consistent with previous evidence for a late Paleoarchean tectono-metamorphic event in the AGC. Subsequent isotopic disturbance of garnet at c. 1.9 Ga is interpreted to correspond to a modification of the primary Lu–Hf systematics in response to garnet resorption/recrystallization during the Paleoproterozoic Wopmay orogeny, resulting in significant scatter between these two age components. Our study adds to the small number of published P–T data for metamorphic rocks older than 2.8 Ga and shows that tonalitic gneisses in the AGC record a high apparent thermal gradient of ~140°C/kbar in the late Paleoarchean. This thermal gradient is the highest among the limited dataset, but is broadly similar to data from other Paleoarchean-Mesoarchean crustal rocks in recording high T/P ratios (>77.5°C/kbar).